2012
DOI: 10.2217/cpr.12.65
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and assisted reproductive technologies

Abstract: SUMMARY Racial and ethnic disparities have been reported in every field of medicine. High costs associated with infertility treatment and restricted access to care has made assisted reproductive technologies particularly susceptible and vulnerable to disparity. Despite advances in the field, emerging literature has continued to demonstrate poorer outcomes in minority women receiving treatment with assisted reproductive technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Asian women seem to have worse outcomes than Caucasian women with similar demographic statistics [29]. Researchers have therefore suggested that Asian race may be an independent risk factor for poor outcome after ART, although the reason for this is still unclear [36].…”
Section: Infertility Treatment and Race/ethnicitymentioning
confidence: 99%
“…Asian women seem to have worse outcomes than Caucasian women with similar demographic statistics [29]. Researchers have therefore suggested that Asian race may be an independent risk factor for poor outcome after ART, although the reason for this is still unclear [36].…”
Section: Infertility Treatment and Race/ethnicitymentioning
confidence: 99%
“…Even when controlling for these factors, some groups continue to have worse outcomes. [5][6][7][8][9][10][11][12][13] Plowden, Novak, and Spong examine these disparities and the possible etiologies of disparate obstetrical outcomes in the article entitled "Disparities in Obstetrical Outcomes in ART Pregnancies Compared with Natural Conceptions. "…”
Section: Obstetricsmentioning
confidence: 99%
“…Despite this, ART patients in general, and African American, Hispanic, and Asian women specifically, have demonstrated poorer obstetric and neonatal outcomes. [9][10][11][12][13][14][15][16][17][18] Higher rates of intrauterine growth retardation (IUGR) and lower rates of live birth have been reported in these women. 13,15,17,18 Preterm deliveries have also been found to be more prevalent in African American and Hispanic women.…”
mentioning
confidence: 99%